IMPLEMENTASI SISTEM KEUANGAN DESA; PENINGKATAN KINERJA APARATUR DESA KAMBINGAN BARAT, KABUPATEN SUMENEP - Ardhiarisca, Oryza (Universitas Cenderawasih, 2024)
This study aims to determine the benefits, as well as improve the performance of West Kambingan Village Apparatuses in the implementation of the SisKeuDes application. The SisKeuDes application is an application that can assist the Village Government in managing village finances. This research method uses a qualitative descriptive approach. Determination of informants using the interview method and selected informants based on the criteria of need. Informants in this study included village heads, village secretaries, chief of finance and village operators. The research data was obtained from interviews and observations. The results of the study show that the SisKeuDes application is very useful and helps the work of village officials. Village financial management becomes more effective and efficient so as to improve the performance of the Kambingan Barat Village Apparatus. Keywords: Village Government, Financial Management, SisKeuDes Application, Village Apparatus